Health Literacy and Health-Promoting Behaviours in Chronic Disease Clients: A Survey of Adults in the North Central Region - Boodoo, Soraya (My University, 2017)
This study examined the relationship between health literacy and health-promoting behaviours among adult chronic-disease clients in the North Central Regional Health Authority of Trinidad and Tobago. Data were collected through questionnaires administered to a representative sample of 153 participants at health centres in the region under study. Analysis of the data revealed that while there was no significant relationship between health literacy and behaviours, or health literacy and gender, health literacy was significantly impacted by factors of age, religion, education level, and medication compliance.
Keywords: Health education; Adult education; Public health; Trinidad and Tobago